On the oppositions that underlie the distinctions displayed by Russian causal clauses - Pekelis Olga (Linguistics)
This article studies Russian causal clauses employing formal contrasts that causal clauses manifest crosslinguistically. I explore two approaches that have been proposed to account for such contrasts: the coordination-subordination approach and the approach assuming that causal clauses represent different classes of adverbial clauses that differ in their degree of syntactic integration with the host clause. It is argued that the Russian data cannot be consistently accounted for unless a combination of the two approaches is applied. The analysis also reveals that the degrees of syntactic integration encoded by Russian causal clauses are different from those claimed for German causal clauses by previous research. Thus, while the degree of syntactic integration proves to be a valid parameter to compare systems of causal clauses crosslinguistically, its specific realizations may vary. Furthermore, the juxtaposition of the two approaches poses the question as to what the difference is between syntactically non-integrated adverbial clauses and coordinated clauses. I tentatively suggest that they too differ in terms of the degree of integration, but this difference belongs to the level of information packaging in discourse and not to the level of syntax.